Rural‐Urban Differences in Positive Childhood Experiences Across a National Sample - Crouch, Elizabeth; Radcliff, Elizabeth; Merrell, Melinda A.; Bennett, Kevin J. (The Journal of rural health, 2021)
Purpose The purpose of this study was to examine the prevalence of positive childhood experience (PCE) and adverse childhood experience (ACE) exposures in 31 states plus the District of Columbia and to estimate exposure differences between rural and urban children. Methods A cross‐sectional study was conducted with a sample of 19,251 respondents from the 2017‐2018 National Survey of Children's Health (NSCH), a nationally representative sample of US children. Sociodemographic information, residence, and PCE and ACE responses were utilized. To calculate frequencies, proportions, and unadjusted associations for each variable, descriptive statistics and bivariate analyses were used. Multivariable regression models were used to examine the association between residence and PCEs that showed significance in bivariate analyses. Findings In adjusted analyses of PCEs, there was no significant difference between rural and urban children for after‐school activities. However, rural children were more likely to volunteer in the community, school, or church than were urban children (aOR 1.32; 95% CI: 1.14‐1.54). Rural children also had greater odds of having a mentor for advice or guidance, compared to urban children (aOR 1.8; 95% CI: 1.40‐2.52). Conclusions An examination of both PCEs and ACEs provides policy makers, program developers, and other stakeholders the opportunity to determine needs of rural children and where to target interventions. Furthering the understanding of PCEs and ACEs is important to bring individuals, families, and communities together to both address childhood adversity and utilize existing family and community‐level assets.